'Maximising shareholder value': a detailed insight into the corporate political activity of the Australian food industry. (22nd January 2017) - Mialon, Melissa; Swinburn, Boyd; Allender, Steven; Sacks, Gary
Abstract: Objective: To gain deeper insight into the corporate political activity (CPA) of the Australian food industry from a public health perspective. Methods: Fifteen interviews with a purposive sample of current and former policy makers, public health advocates and academics who have closely interacted with food industry representatives or observed food industry behaviours. Results: All participants reported having directly experienced the CPA of the food industry during their careers, with the 'information and messaging' and 'constituency building' strategies most prominent. Participants expressed concern that food industry CPA strategies resulted in weakened policy responses to addressing diet‐related disease. Conclusions: This study provides direct evidence of food industry practices that have the potential to shape public health‐related policies and programs in Australia in ways that favour business interests at the expense of population health. Implications for public health: This evidence can inform policy makers and public health advocates and be used to adopt measures to ensure that public interests are put at the forefront as part of the policy development and implementation process.